Comparison of Institutional Empirical Cephalosporin Therapy Protocol versus Standardized International Sepsis in Obstetrics Protocol in Managing Sepsis during Pregnancy and Postpartum - Kalpana L, Kalpana L; Parimala, Parimala (Journal of Neonatal Surgery, 2025)
Background: Maternal sepsis remains a leading cause of pregnancy-related mortality, contributing to 11% of global maternal deaths. While international sepsis guidelines exist, many institutions continue using empirical cephalosporin protocols despite growing antimicrobial resistance concerns. This study compared clinical and economic outcomes between institutional empirical cephalosporin therapy and standardized international sepsis protocols in obstetric patients. Methods: A randomized controlled trial was conducted with 500 pregnant/postpartum women diagnosed with sepsis (SOFA score ≥2) at a tertiary care center. Participants were allocated to: Group A (n=250): Institutional protocol (cefoperazone-sulbactam empirical therapy). Group B (n=250): International protocol (WHO/Surviving Sepsis Campaign guidelines). Primary outcomes included clinical recovery and mortality. Secondary outcomes assessed antimicrobial resistance, healthcare utilization, and cost-effectiveness (converted to INR). Statistical analysis employed t-tests, chi-square, and Kaplan-Meier methods (SPSS v26). Results: The international protocol demonstrated superior outcomes: 28% lower mortality (4% vs 8%, p=0.04). Faster clinical improvement (3.8 vs 4.5 days, p=0.02). 37% reduction in resistant isolates (22% vs 35%, p=0.003). 17% shorter hospital stays (6.2 vs 7.5 days, p=0.001). 21% cost savings (₹1,82,600 vs ₹2,32,400 per case, p=0.001). Conclusion: Standardized international sepsis protocols significantly improved survival, reduced antimicrobial resistance, and decreased healthcare costs compared to institutional cephalosporin-based regimens. These findings support global guideline adoption in obstetric practice, particularly in resource-limited settings. Future research should explore implementation strategies across diverse healthcare systems.